Convergence of public library spaces in South Korea: User insights on motivations and collaboration - Jeong, Yongsun; Na, Kyoungsik; Lee, Jisu (Malaysian Journal of Library and Information Science, 2024)
This study explores the evolving role and function of public libraries as essential physical spaces in the information age, with a focus on user perspectives regarding the need for convergence and collaboration within library spaces and potential approaches for implementing this convergence in South Korea. Using a qualitative approach, interviews were conducted with 58 university students in their 20s and 30s who have experience using public libraries. Findings indicate that users view convergence as a way for public libraries to remain relevant by integrating various services and fostering partnerships that enhance community engagement. These insights provide practical recommendations for library administrators and policymakers on physical and institutional convergence strategies in public libraries, contributing valuable knowledge to this evolving area.